Distinctive Effects of Cytochalasin B in Chick Primary Myoblasts and Fibroblasts - Ojima, Koichi (PLoS One, 2016)
Actin-based structures play fundamental roles in cellular functions. However it remains controversial how cells cope with the absence of F-actin structures. This report focuses on short- and long-term effects of cytochalasin B (CB) on actin-complexes in fibroblasts and myoblasts. Thirty min of CB treatment dispersed subplasma actin cortices, lamellipodia, ruffled membranes, stress fibers and adhesion plaques into actin patches in fibroblasts and muscle cells. In contrast, 72 hrs CB treatment showed distinct morphological effects. Fibroblasts became giant multinucleated-finger shaped with 5 to 10 protrusions, 3–8 μm in width, and >200 μm in length. They lacked cortical actin, stress fibers, adhesion plaques and ruffled membranes but contained immense lamelliopodia with abnormal adhesion plaque protein complexes. Muscle cells transformed into multinucleated globular-shaped but contained normal I-Z-I and A-bands, indicating that CB did not interfere with the assembly of myofibrils. Within 30 min after CB removal, finger-shaped fibroblasts returned to their original shape and actin-containing structures rapidly reappeared, whereas muscle cells respond slowly to form elongated myotubes following CB washout. The capacity to grow, complete several nuclear cycles, assemble intermediate filaments and microtubules without a morphologically recognizable actin cytoskeleton raises interesting issues related to the role of the actin compartments in eukaryotic cells.